A Framework for Triple-Entry Bookkeeping - Ijiri, Yuji (The Accounting Review, 1986)
[Building upon the author's earlier work [1982], which demonstrated that double-entry bookkeeping is not an absolute system defying extensions but is logically extendible to triple-entry bookkeeping, this paper develops a framework for a triple-entry bookkeeping system and illustrates it by means of a simple example which includes a worksheet, journal entries, and three basic financial statements-wealth statement, momentum statement, and force statement. While the earlier work extended the existing two dimensions of bookkeeping (wealth and income) into a third dimension under the same measurement unit, namely dollars, this present paper introduces "momentum accounting" under a related but different measurement unit, namely dollars per time period, such as a month, in such a way that, when mathematically integrated over time, momentum accounting articulates with wealth accounting in every dimension. Dealing with earnings rates per time period associated with assets and liabilities, momentum accounting accounts for earnings rates and their changes. Finally, "force accounting" is introduced as the third layer of the accounting system to explain factors that are judged to be responsible for changes in the earnings rate. Its measurement (dollars per month per month, for example) is induced by the measurement in momentum accounting, which in turn is induced by the measurement in wealth accounting. In this way, the extension of double-entry bookkeeping is carried out under a disciplined framework of measurements, which hopefully will direct management's attention and sensitivity to factors at a level deeper than the level of wealth and income that has been traditionally dealt with by double-entry bookkeeping.]